134 Vegetation characteristics and diurnal periods influenced the landscape-use pattern of goats and sheep in woodlands. (29th July 2019) - Bhattrai, Shailes; Karki, Uma; Poudel, Sanjok
Abstract: Woodlands dominate the landcover in the Southeast and offer great opportunities for expanding small-ruminant grazing. However, unmanaged understory shrubs grown beyond animals' access minimizes the utilization of such vegetation. Managing the understory shrubs and non-target trees to lower heights may increase animals' access to woodland vegetation and alter the landscape-use patterns of animals. The study objective was to determine the effect of vegetation height on the behavior and distribution of Kiko wethers and Katahdin rams in woodlands. The study was conducted in six woodland plots (0.4-ha each) containing southern pine and hardwood trees and numerous understory vegetation. The non-pine species were either cut to one of the heights from the ground level (0 m, 0.91 m, 1.52 m) or left uncut (control). Once the cut vegetation grew back and attained the full canopy, Kiko wethers (8, 48–50 months old, 72.8 ± 2.29 kg live weight) and Katahdin rams (5, 29–32 months old, 95.5 ± 4.31 kg live weight) were rotationally stocked in separate plots (3 plots each species), and their diurnal (dawn-dusk) behaviors and distribution patterns monitored when they were in each plot during the summer of 2018. Data were analyzed in Kruskal-Wallis rank sum test in R. Both wethers and rams visited the control treatment the least, rams grazed mostly in areas with short vegetation (0 m), and wethers visited more to areas with higher vegetation (1.52 m) than rams for feeding (P < 0.001), which was predominant during the post-midday period (3:00-dusk) (P < 0.0001). Browsing was the dominant feeding behavior of wethers (39% browsing vs. 4% grazing), while rams' feeding behavior was dominated with grazing (24% grazing vs. 12% browsing). Lying was the dominant diurnal behavior of both wethers (46%) and rams (35%), and predominant during the midday period (11 a.m.-3:00 p.m.) (P <0.05). Vegetation heights and diurnal period highly influenced animals' behavior.